2005
DOI: 10.1074/jbc.m503897200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Role of the Rab GTPase-activating Protein AS160 in Insulin-regulated GLUT4 Trafficking

Abstract: Insulin stimulates the translocation of the glucose transporter GLUT4 from intracellular vesicles to the plasma membrane. In the present study we have conducted a comprehensive proteomic analysis of affinity-purified GLUT4 vesicles from 3T3-L1 adipocytes to discover potential regulators of GLUT4 trafficking. In addition to previously identified components of GLUT4 storage vesicles including the insulin-regulated aminopeptidase insulin-regulated aminopeptidase and the vesicle soluble N-ethylmaleimide factor att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
418
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(455 citation statements)
references
References 83 publications
(75 reference statements)
27
418
1
1
Order By: Relevance
“…AS160 (Akt substrate of 160 kDa) is a Rab GTPase activating protein (RabGAP), and the Arg 973 residue on human AS160 functions as a key residue to maintain its GAP activity (5,6). In 3T3-L1 adipocytes and L6 myocytes, AS160 is required for intracellular retention of GLUT4 under basal conditions (5,(7)(8)(9). Insulin stimulates the phosphorylation of AS160 via protein kinase B (PKB), and the phosphorylation of AS160 inactivates its GAP activity (10) and promotes GLUT4 translocation onto the cell surface (5,(11)(12)(13).…”
mentioning
confidence: 99%
“…AS160 (Akt substrate of 160 kDa) is a Rab GTPase activating protein (RabGAP), and the Arg 973 residue on human AS160 functions as a key residue to maintain its GAP activity (5,6). In 3T3-L1 adipocytes and L6 myocytes, AS160 is required for intracellular retention of GLUT4 under basal conditions (5,(7)(8)(9). Insulin stimulates the phosphorylation of AS160 via protein kinase B (PKB), and the phosphorylation of AS160 inactivates its GAP activity (10) and promotes GLUT4 translocation onto the cell surface (5,(11)(12)(13).…”
mentioning
confidence: 99%
“…Thus, AS160 is thought to regulate the GTPase activity of Rab proteins to inhibit GLUT4 vesicle movement to, and/or fusion with, the plasma membrane. 53,54 Phosphorylation of AS160 on one or more of the eight described phosphorylation sites by Akt inhibits its GTPase activating protein activity, such that in response to insulin, the GTP form of Rab proteins is elevated leading to an increased number of GLUT4 molecules in the plasma membrane. A recent study provided evidence that AS160 is involved in both insulin-and contraction-stimulated glucose uptake in skeletal muscle.…”
Section: Involvement Of Ampk In Mitochondrial Biogenesis In Skeletal mentioning
confidence: 99%
“…Tbc1d4 has GAP activity with the Rabs 2A, 8A, 8B, 10 and 14. Rabs 10 and 14 have been shown to be present on GLUT4 vesicles and therefore these may be the important target Rabs that lie between Tbc1d4 and regulated GLUT4 vesicle activity [2,3]. Lienhard's hypothesis that links Tbc1d4 activity to both insulin signalling and GLUT4 vesicle activity is shown in Figure 1.…”
mentioning
confidence: 99%
“…It cannot then act on it to convert it into its non-functional GDP form. It has been shown that Tbc1d4 may be localized to GLUT4 vesicles by virtue of its binding to cargo proteins within the GLUT4 vesicles [3,4]. The change in localization of Tbc1d4 initiated by phosphorylation may involve its association with a 14-3-3 protein and subsequent dissociation from the GLUT4 vesicles and into the cytoplasm [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation